2010
DOI: 10.1139/y10-040
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1-mediated cerebrovascular remodeling is not associated with increased ischemic brain injury in diabetesThis article is one of a selection of papers published in the two-part special issue entitled 20 Years of Endothelin Research.

Abstract: Diabetes increases the risk as well as the poor outcome of stroke. Matrix metalloprotease (MMP) activation disrupts blood-brain barrier integrity after cerebral ischemia. We have previously shown that type 2 diabetes promotes remodeling of middle cerebral arteries (MCA) characterized by increased media:lumen (M/L) ratio and MMP activity in an endothelin (ET)-1-dependent manner in the Goto-Kakizaki (GK) rat model. In the present study, we examined the effects of ET-1-mediated vascular remodeling on neurovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…The vascular remodeling was associated with impaired myogenic reactivity and decreased cerebral blood flow (Kelly-Cobbs et al, 2011b). Our results also showed that hyperglycemia-mediated upregulation of the ET system plays a critical role in the development of vascular remodeling where glycemic control or dual ET-1 antagonism prevented diabetes-induced remodeling (Kelly-Cobbs et al, 2011a, Kelly-Cobbs, Harris, 2011b, Li, Kelly-Cobbs, 2010, Sachidanandam et al, 2009a). Accordingly, the first goal of this study was to determine whether and to what extent this remodeling continues to progress and whether it can be reversed if treatment is started late in the disease.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…The vascular remodeling was associated with impaired myogenic reactivity and decreased cerebral blood flow (Kelly-Cobbs et al, 2011b). Our results also showed that hyperglycemia-mediated upregulation of the ET system plays a critical role in the development of vascular remodeling where glycemic control or dual ET-1 antagonism prevented diabetes-induced remodeling (Kelly-Cobbs et al, 2011a, Kelly-Cobbs, Harris, 2011b, Li, Kelly-Cobbs, 2010, Sachidanandam et al, 2009a). Accordingly, the first goal of this study was to determine whether and to what extent this remodeling continues to progress and whether it can be reversed if treatment is started late in the disease.…”
Section: Introductionsupporting
confidence: 65%
“…Within the cerebrovasculature, this remodeling was associated with impaired myogenic reactivity, decreased tone, and decrease in cerebral blood flow (Kelly-Cobbs, Elgebaly, 2011a). We have recently showed that glycemic control with metformin or dual receptor antagonism by bosentan can prevent large artery remodeling and improves myogenic function (Li, Kelly-Cobbs, 2010, Sachidanandam et al, 2008, Sachidanandam, Hutchinson, 2009a, Sachidanandam et al, 2009b, Sachidanandam, Portik-Dobos, 2010). While these results provided important information with regard to use of these agents for preventive strategies in diabetes, the therapeutic potential remained undefined and the current study now provides evidence that established pathological remodeling in diabetes can be at least partially reversed by these approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ET appears involved in hypertension-induced hypertrophy of cerebral arteries without changing their distensibility [240]. Diabetic mice can also display increased ET receptor levels and ET-1 dependent matrix metalloproteinase activation, which can facilitate cerebrovascular remodeling, especially after hypoxic exposure [241, 242]. Through binding to ETA receptor, increased ET levels can activate the transcription factor Nuclear Factor of Activated T cells, isoform 3 (NFAT3), resulting in hypertension and vascular remodeling.…”
Section: Receptor Tyrosine Kinase-independent Vasotrophic Factorsmentioning
confidence: 99%
“…In contrast, neovascularization in the brain may be augmented yet still dysfunctional [107]. This condition manifests as an increased media-lumen ratio, a compromised BBB and increased activity of matrix mattaloproteinases (MMP) [108]. Therefore, inflammation- activated microglial cells and invading macrophages play important roles in altered neurovascular coupling, BBB permeability and, ultimately, neuronal loss.…”
Section: Cerebromicrovascular Disease Vasoreactivity and Brain Atrophymentioning
confidence: 99%